2010
DOI: 10.9744/ing.v11i2.17892
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of L1 in EFL Teaching

Abstract: This study is conducted in a classroom action research to improve the students' achievement in writing English sentences in Present Perfect Tense in Structure 1 lessons. The subject consisted of 20 Semester II students who took Structure I lessons in English Education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Zacharias' (2003) research showed tertiary education English teachers' account about the possible uses of MT in the process of teaching EFL, including explaining the new words meaning and grammatical points, giving instructions, checking learners' understanding and giving feedback to individual learners. Usadiati's (2009) study revealed that the use of Indonesian interchangeably with English in the explanations of concepts and rules for teaching students to write English sentences in Present Perfect Tense improved the students' achievement.…”
Section: Introductionmentioning
confidence: 91%
“…Zacharias' (2003) research showed tertiary education English teachers' account about the possible uses of MT in the process of teaching EFL, including explaining the new words meaning and grammatical points, giving instructions, checking learners' understanding and giving feedback to individual learners. Usadiati's (2009) study revealed that the use of Indonesian interchangeably with English in the explanations of concepts and rules for teaching students to write English sentences in Present Perfect Tense improved the students' achievement.…”
Section: Introductionmentioning
confidence: 91%
“…However, studies investigate the use of Bahasa Indonesia in English classes, particularly in senior high school level, are still limited. Related previous studies (Julianti, Atmowardoyo & Mahmud, 2016;Resmini, 2019;Usadiati, 2009;Zacharias, 2003) were conducted in tertiary education level. Only a few studies (Anggrahini, 2019;Hasrina, Aziz & Fitriani, 2018;and Pardede, 2018) focused on senior high school students.…”
Section: Introductionmentioning
confidence: 96%
“…Studies investigating teachers' perception (Anh, 2010;Pardede, 2018) supported the judicious use of the first language in some situations in the English classes. Usadiati's (2009) study revealed that Bahasa Indonesia is used interchangeably with English for explaining concepts and rules for teaching writing English sentences to improve the students' achievement. Fist language appeared to be very advantageous in the activities of explaining complex concepts, checking learners' understanding, giving feedback to individual learners, and learning new vocabulary, especially abstract words.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, "not making use of both the L1 and L2 in the classroom is a waste of a valuable resource" (Turnbull, 2018, p.55). Hence, L1 has already been used in English language classes, and ESP classroom is not an exception, as it facilitates learners" understanding and provides sense of security, better comprehension and progress, higher achievement, and a positive learning atmosphere (Auerbach, 1993;Bruen & Kelly, 2017;Butzkamm, 2003;Usadiati, 2009). L1 also contributes to language skills development, metalinguistic awareness, negotiation of meaning, reduced cognitive overload, lower affective barriers such as anxiety, and higher self-confidence and self-motivation (Berning, 2016;Boustani, 2019;Bruen & Kelly, 2017;Cheng, 2015;Cuartas Alvarez, 2014;Luchini & Rosello, 2007;Usadiati, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, L1 has already been used in English language classes, and ESP classroom is not an exception, as it facilitates learners" understanding and provides sense of security, better comprehension and progress, higher achievement, and a positive learning atmosphere (Auerbach, 1993;Bruen & Kelly, 2017;Butzkamm, 2003;Usadiati, 2009). L1 also contributes to language skills development, metalinguistic awareness, negotiation of meaning, reduced cognitive overload, lower affective barriers such as anxiety, and higher self-confidence and self-motivation (Berning, 2016;Boustani, 2019;Bruen & Kelly, 2017;Cheng, 2015;Cuartas Alvarez, 2014;Luchini & Rosello, 2007;Usadiati, 2009). Therefore, although "the use of L1 has been gradually viewed less favorably by second language (L2) teaching theorists after the Grammar-Translation Method lost its prominent role" (Du, 2016, p.359), the interest regarding whether to include learners" L1 in teaching has gained recognition and become a persistent research topic particularly after being neglected for many years within the communicative approach beginning in 1970s.…”
Section: Introductionmentioning
confidence: 99%